P499 Accessing ultrasonographic transmural healing in patients with Crohn's disease after induction therapy with infliximab: should we aim for higher infliximab trough levels?. (21st January 2022) - Morão, B; Frias Gomes, C; Revés, J; Cúrdia Gonçalves, T; Freitas, M; Castro, F; Moreira, M J; Cotter, J; Pereira, F; Caldeira, A; Sousa, R; Coelho, R; et al.
Abstract: Background: Higher infliximab trough levels (ITL) have been shown to be associated with better rates of clinical remission and mucosal healing. Transmural healing (TMH) assessed by cross-sectional imaging [such as intestinal ultrasound (IUS)] is emerging as a potential target in Crohn′s disease (CD) treatment, but whether there is any relation with ITL remains unclear. Our goal was to investigate the association between ITL and bowel wall thickness (BWT) in patients with CD after induction therapy with IFX. Methods: Prospective multicentric cohort study of CD patients who started IFX in mono or combination therapy. Patients performed IUS and ITL at weeks 0 and 14. TMH was defined as BWT ≤3 mm in the most affected segment. A ROC curve was plotted to determine the best cut-off point of ITL to predict TMH. Chi-square test, Mann-Whitney test and Spearman correlation were performed to assess the ITL relation with BWT. Results: We included 57 patients, 30 (53%) of whom were men with mean age of 36±15 years. Disease extension according to Montreal classification was L1 in 19 (33%), L2 in 8 (14%) and L3 in 30 (53%) patients; 6 (11%) patients also had L4 extension and 19 (33%) patients had perianal disease. Disease behavior was B1 in 36 (63%), B2 in 13 (23%) and B3 in 8 (14%) of patients. Most patients (61%) were under immunomodulators and 15 (26%) were under corticosteroids when infliximab was started; most (88%) were naïve for infliximab. At week 0, all patients had endoscopic activity and 97% had increased BWT at the most affected segment. The most affected segment on IUS at week 0 was the terminal ileum in 38 (67%) patients and the ascending, transverse, descending and sigmoid colon in 5 (9%), 2 (3%), 7 (12%) and 5 (9%) patients, respectively. There was a very good agreement between IUS and colonoscopy for evaluation of the most affected segment at baseline (kappa 0.81, p<0.001). Median ITL at week 14 was 4.30 μg/ml (IQR 0.01–21). TMH at week 14 was achieved in 13 (23%) patients. ITL and BWT at week 14 were negatively correlated, with a fair correlation (r=-0.3, p=0.03). The AUC of ITL for BWT was 0.661 (best cut-off value 7.65, sensitivity 54%, specificity 89%). ITL ≥7.65 μg/ml was associated with higher rates of TMH (44% vs 15%, OR 4.47 [95%CI 1.2–16.4], p=0.04). Conclusion: In our cohort of CD patients completing induction therapy with infliximab, higher ITL were associated with higher ultrasonographic transmural healing rates. The best cut-off for predicting TMH was ITL above 7.65μg/ml.